Penyidikan Tindak Pidana Pungutan Liar Pemasangan Listrik Di Kejaksaan Negeri Taluk Kuantan - Setiawan, Eko Wira; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
One of the most crime that is worst between the other crimes that happen is extortion.Just like the other crimes, extortion is crimes againts legal norms that should be interpreted asan acts that harms the victim. The problem is personal procurement personnel prosecutor asinvestigator of extortion crime limited due to knowing at an early stage about some criminalact. This matters cannot be left out without any legal settlement of such a crime. Thereforeany criminal efforts committed by anyone must be dealt firmly irrespective of status.The problem in this research is 1) How is the investigation of criminal extortionelectrical installation in The State Judiciary of Taluk Kuantan? 2) What is the problems ininvestigation of criminal extortion electrical installation in The State Judiciary of TalukKuantan? 3) How the effort made to overcoming the problems of the investigation of criminalextortion in The State Judiciary of Taluk Kuantan? The research method in this research issociological. The location of this research is done in the state Judiciaryâs jurisdiction of TalukKuantan. The population in this study is the head of Intelligence of The State Judiciary ofTaluk Kuantan, The State Judiciaryâs investigator of Taluk Kuantan, and victims of criminalextortion electrical installation. The data source nature of this study are primary andsecondary data sources with data collection techniques such as interviews, review of theliterature. The data obtained will be analyzed using qualitative methods.Overview common in this study is an overview of a crime, an overview of theinvestigation and an overview of extortion . An overview of the crime of discussing thenotion of crime, the elements of a criminal offense . An overview of the investigation todiscuss the duties and authority of the investigator, efforts in the investigation . An overviewof extortion discuss the notion of extortion, criminal extortion provisions , criminal andconviction of the crime of extortion.Investigation of criminal extortion electrical installation by The State Jusdiciary ofTaluk Kuantan there are obstacles that proved some cases handled by investigators halted dueto incomplete evidence. Obstacles in the criminal investigation of extortion by The StateJudiciary of Taluk Kuantan is the lack of quantity and quality of personnel in Riau Police SubDirectorate II Special Criminal Investigation Directorate, facilities are inadequate for TheState Judiciary of Taluk Kuantan, lack of participation and of the public in any jurisdiction inThe State Judiciary of Taluk Kuantan. Attempts by investigators in overcoming the problemsfaced by investigators of criminal extortion electrical installation by The State Judiciary ofTaluk Kuantan is preventive, repressive, and Increase participantion communities in TheState Judiciary of Taluk Kuantan jurisdiction.Keywords : Investigation - Crime â Extortion- Judiciary